Pelatihan Fitur Mockup Serta Desain Pamflet Dengan Aplikasi Photoshop - Ramos, Samuel; Sharyanto; Gunawan Sudarsono, Bernadus (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2022)
The development of information and communication technology is so rapid that it touches all human activities. Information technology in the form of applications is very much needed both individually and in groups. One application that is needed and can become a job is Graphic Design. Graphic design application is an application that is used to design or design an object in accordance with the wishes and imagination. One application that is widely used to design objects is the Photoshop application. If someone has a talent for painting, drawing and the like, the Photoshop application is perfect for use. And if occupied will become a professional designer in the field of Graphics. The purpose of this activity is to provide knowledge to the Karang Taruna RW 17 group and surrounding youth in making mockups and pamphlets independently using the Photoshop application. The method used is a presentation and training in the form of simulation or direct practice using the Photoshop application. The result of this training activity is that all participants are able to use the Photoshop application in designing pamphlets independently according to the talents and imagination of the participants. Keywords: Graphic Design, Mockup, Pamphlet, Photoshop